Profitable partnerships: The Chinese business elite and Dutch lawyers in the making of Semarang. (June 2021) - Post, Peter
Abstract : This article examines the collaboration between the law firm of C.W. Baron van Heeckeren from Semarang and the Oei Tiong Ham Concern (OTHC). From the 1880s this Dutch law firm became the centre of a close-knit group of Dutch lawyer-entrepreneurs who through interlocking business directorships developed important sectors of the Javanese economy and the city of Semarang. In doing so Van Heeckeren and his associates teamed up with the Chinese business elite of the port-city. In particular they worked with the foremost Overseas Chinese capitalist, Major Oei Tiong Ham, developing profitable partnerships. The Dutch lawyers acted not only as his legal advisors, but developed his sugar empire as directors-shareholders, held major stakes in his shipping business and coolie trade, and profited from his opium trade. They moreover helped Oei Tiong Ham to acquire real estate and enterprises formerly belonging to powerful Chinese opium farmers and collaborated with him in developing infrastructural and housing projects. This article provides new and revealing details about how the business world of colonial Java worked during the early phase of Dutch economic imperialism and how the Chinese business elite seized the opportunities provided by the Dutch colonial state to advance their business interests.